2022
DOI: 10.1007/s13311-021-01170-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Impairment (VCI)

Abstract: Vascular cognitive impairment (VCI) is predominately caused by vascular risk factors and cerebrovascular disease. VCI includes a broad spectrum of cognitive disorders, from mild cognitive impairment to vascular dementia caused by ischemic or hemorrhagic stroke, and vascular factors alone or in a combination with neurodegeneration including Alzheimer's disease (AD) and AD-related dementia. VCI accounts for at least 20-40% of all dementia diagnosis. Growing evidence indicates that cerebrovascular pathology is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 299 publications
0
60
0
20
Order By: Relevance
“…Hypertension is a major risk factor for vascular dementia ( 37 , 38 ). Previous studies have shown that changes in blood pressure are associated with changes in cerebral perfusion and metabolism ( 5 , 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a major risk factor for vascular dementia ( 37 , 38 ). Previous studies have shown that changes in blood pressure are associated with changes in cerebral perfusion and metabolism ( 5 , 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…VCI may be used to describe any cognitive impairments that are associated with cerebrovascular disease, and hypoperfusion has been identified as one of the main culprits of VCI. VCI ranges from mild cognitive impairments to vascular dementia that is caused by ischemic or hemorrhagic stroke and vascular factors alone or in a combination with neurodegeneration such as that from AD (Roman, 2002;Rundek et al, 2021). Cerebral hypoperfusion will lead to blood-barrier disruption, microglial activation, matrix metalloproteinase activation, white matter lesions, and ultimately, cognitive impairment due to chronic glucose and oxygen deficiency in parenchymal tissue (Swartz et al, 2003;Kitamura et al, 2012;Liu and Zhang, 2012;Zietemann et al, 2016;Duncombe et al, 2017;Zilberter and Zilberter, 2017).…”
Section: Understanding Cognitive Deficits In Dementiamentioning
confidence: 99%
“…A growing amount of evidence from animal models and epidemiological investigations in humans suggests that chronic cerebral hypoperfusion (CCH) is one of the major pathophysiological hallmarks of cognitive decline ( Washida et al, 2019 ; Zlokovic et al, 2020 ; Rundek et al, 2021 ). CCH, despite without a clear definition, is implicated in multiple morbid conditions like heart failure, hypotension, and carotid stenosis ( Iturria-Medina et al, 2016 ; Ciacciarelli et al, 2020 ), whose relationships to cognitive function have been verified in previous research.…”
Section: Introductionmentioning
confidence: 99%